Kesadaran Historis (Empat Dasar Pemikiran) Teologi Islam dalam Pandangan Hassan Hanafi - Tarigan, Mardinal; Br Sembiring, Rahmadani; Rizekuna, Rizekuna (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The science of monotheism is the most fundamental thing for all Muslims. This is because monotheism plays an important role in human life. However, at this time monotheism, which was once strongly believed by all the people of the prophet Muhammad, has brought stagnation to Islamic thought influenced by scholars who still base their beliefs on classical Islamic theology. The purpose of this study is to discuss the formulation of the concept of monotheism initiated by Hassan Hanafi. The method used is the character study method with a qualitative type by raising one of the Islamic thinkers. In making this journal, researchers used the first method used to analyze the thoughts of figures who aims to explain the results of his thoughts objectively. The second method is used as a tool or medium to analyze the data he has obtained, Hassan Hanafi also tries to formulate his concept of monotheism so as not to exclude monotheism from the problems of life. The Qur'an as the basis of awareness must first ensure the purity of the text. Which can be seen through historical stories from the time of the previous prophets to the present. A person who compiles books on the Qur'an must be responsible for the originality of writing the words of Revelation as the story was revealed directly to the prophet Muhammad through the angel Gabriel.